Political participation Institution or institution? Elements for reflection - Eulalia Borja Bedoya; Daniela Barrera Machado; Alfonso Insuasty Rodríguez (Ratio Juris, 2017)
Participation becomes a fundamental process to build a project of asociety in dignity and peace. Hence the importance of analyzing the  process of instituted and instituted political participation, in light of its dynamics and implications in terms of political culture. The above in order to highlight the need to strengthen institutional participation, and generate popular power with the possibility of having an impact on the public agenda, and the generation of structural changes in societies.